2022
DOI: 10.1101/2022.03.04.22271890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective antibodies and T cell responses to Omicron variant three months after the booster dose of BNT162b2 vaccine

Abstract: The high number of mutations in the Omicron variant of SARS-CoV-2 cause its immune escape when compared to the earlier variants of concern (VOC). At least three vaccine doses are required for the induction of Omicron neutralizing antibodies and further reducing the risk for hospitalization. However, most of the studies have focused on the immediate response after the booster vaccination while the duration of immune response is less known. We here studied longitudinal serum samples from the vaccinated individua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… 71 Overall, this investigation showcases that vaccinated individuals after a second dose were seen to have stronger specific memory T‐cell responses against the SARS‐CoV‐2 virus, and this was further elevated after the third vaccination along with the long time presence of both CD4 + and CD8 + levels with a little lower response towards Omicron variant. 71 …”
Section: T‐cell Immunity Against Sars‐cov‐2 Omicronmentioning
confidence: 62%
See 2 more Smart Citations
“… 71 Overall, this investigation showcases that vaccinated individuals after a second dose were seen to have stronger specific memory T‐cell responses against the SARS‐CoV‐2 virus, and this was further elevated after the third vaccination along with the long time presence of both CD4 + and CD8 + levels with a little lower response towards Omicron variant. 71 …”
Section: T‐cell Immunity Against Sars‐cov‐2 Omicronmentioning
confidence: 62%
“…In another study by Paul Naaber et al, where T‐cell response against Omicron was studied after the booster dose, here participants were vaccinated with two doses of BNT162b2 vaccine and after a gap period of 9 months were vaccinated with a booster dose from BNT162b2, before the booster vaccination the Spike‐RBD immunoglobulin G (IgG) was seen to be in decline after second vaccination but 2 weeks after the booster dose the IgG levels were found to be higher than the previous level, however, 3 months after the booster dose the IgG level was seen to be lower in comparison to its initial levels. In this study, 71 Omicron‐specific CD4 + and CD8 + T‐cell responses and activation‐induced marker (AIM) memory T cells in CD4 + and CD8 + T cells were investigated after the second vaccination and after the third/booster vaccination. Before the administering the third dose the 84% of vaccinated participants were found to have CD4 + memory response and 58% of participants with CD8 + memory response after the booster dose the number was increased to 100% in CD4 + and 90% CD8 + and the Spike‐specific T cells were found to be higher after 2 weeks of booster dose in CD4 + in comparison with CD8 + levels and after 3 months of booster vaccination the Spike specific CD4 + T cells were still present in vaccinees 71 .…”
Section: T‐cell Immunity Against Sars‐cov‐2 Omicronmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies evaluating the effect of vaccination on previously infected individuals reported that antibody levels peaked after three immune stimuli, either by vaccine or infection, without any significant increment after a fourth stimulus [ 21 , 22 ]. On the other hand, cellular immunity seems to stay robust against the Omicron variant after 3 months [ 23 ]. It plays a significant role in protecting against severe disease [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a significant role in protecting against severe disease [ 24 , 25 ]. It likely will stay highly effective against variants of the SARS-CoV-2 virus due to the capacity of T cells to still recognize mutated epitopes from SARS-CoV-2 [ 23 , 25 , 26 ]. Consistent with data on cellular immunity, we observed a slight waning of protection against severe outcomes in the Omicron period.…”
Section: Discussionmentioning
confidence: 99%